Perspektif Hukum Adat Terhadap Upaya Penanggulangan Kekerasan Dalam Rumah Tangga - Agustinus Suwandi Ujang Uhing; Diah Imaningrum S; Hermanto Silalahi (Universitas Katolik Widya Karya Malang, 2024)
Domestic violence in the household often occurs due to various economic factors, early marriage, infidelity. This research resolves domestic violence according to Dayak U'UD Danum customary law in Buntut Purun Village, Ambalau District, West Kalimantan. The method used is empirical legal research with a socological approach. From the phenomena obtained in the field, it is known that the forms of domestic violence in the Dayak U'UD Danum custom are slapped, choked, beaten, slammed and kicked. The factors that cause domestic violence in the community in Buntut Purun Village are economic factors, early marriage, jealousy and infidelity. The efforts of the customary leader in resolving cases of domestic violence in Buntut Purun village are by conducting customary law hearings for victims and perpetrators and imposing sanctions on the perpetrators, and the perpetrators are required to compensate in accordance with Dayak U'UD Danum customary law.